The Essence of The Principle of Presumption of Innocence (The Peerian Journal, 2023)
This article discusses the content of the principle of presumption of innocence, its definition in the legislation of the Republic of Uzbekistan, the history and emergence of this principle, its legal nature. Also, the provisions directly related to this principle and the proposed changes to the Constitution of the Republic of Uzbekistan were analyzed